Assessing the impact of income generating activities toward development of coastal communities in Tanzania: A case of Pangani District council, Tanzania - Kaskazi, Rose P. (2024)
A dissertation submitted in partial fulfillment of the requirements for the award of Master of Public Administration (MPA) of Mzumbe University (MU)